Anterior restorations in bleached teeth: Difficulty establishing the color after bleaching - Santezi, Carolina [UNESP]; Tonetto, Mateus Rodrigues [UNESP]; Presoto, Cristina Dupim [UNESP]; Jassé, Fernanda Ferreira [UNESP]; Oliveira Junior, Osmir Batista de [UNESP]; Andrade, Marcelo Ferrarezi de [UNESP]; Leonardo, Renato de Toledo [UNESP] (Jaypee Brothers Medical Publishing, 2012)
It is becoming more common for patients to look for cosmetic procedures in dental offices. The search for lost or desired esthetics by patients is increasingly frequent and the professional must be able to meet this demand. To do this, dentists not only need to return the tooth back to its normal functioning state but also promote esthetic excellence. In this context, the association of cosmetic procedures, such as teeth whitening and restorative procedures, such as direct adhesive restorations is very common. The composite resins employed nowadays allow the reproduction of various optical properties of natural teeth. With these composite resins, it is possible to reproduce features such as translucency, opacity and specific features of the dental element, to bring back the esthetic harmony of the smile. This article reports a clinical case demonstrating the placement, in a stratified manner, of composite resins in bleached teeth, as well as the reproduction of optical and natural aspects of the teeth. In order to achieve esthetic and functional success of the restored procedure, it is important to be familiar with the new techniques and new materials in the marketand above all, we must know when and where to use them.
Keywords: Bleached teeth; Composite resin.; Dental esthetics; dental material; Filtek Supreme; filtek Z350; phosphoric acid; resin; adult; case report; chemistry; color; dental acid etching; dental procedure; dental surgery; dentin; enamel; histology; human; incisor; male; methodology; prosthesis; tooth; tooth brushing; tooth prosthesis; Acid Etching, Dental; Color; Composite Resins; Dental Enamel; Dental Materials; Dental Polishing; Dental Prosthesis Design; Dental Restoration, Permanent; Dentin; Esthetics, Dental; Humans; Incisor; Male; Phosphoric Acids; Prosthesis Coloring; Tooth; Tooth Bleaching; Young Adult